2006
DOI: 10.1002/jbt.20113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the paratemnus elongatus pseudoscorpion venom in the uptake and binding of the L‐glutamate and GABA from rat cerebral cortex

Abstract: L-Glu is the most important and widespread excitatory neurotransmitter of the vertebrates. Four types of receptors for L-glu have been described. This neurotransmitter modulates several neuronal processes, and its dysfunction causes chronic and acute diseases. L-Glu action is terminated by five distinct transporters. Antagonists for these receptors and modulators of these transporters have anticonvulsant and neuroprotective potentials, as observed with the acylpoliamines and peptides isolated from spiders, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…However, its similarity to other agatoxins, a family of peptides including low mass molecular toxins with affinity to the sodium or calcium ion channels [ 40 ], suggest they might share similar functions. The only previous study on the effects of the crude venom of pseudoscorpion suggested the presence of putative neurotoxins of peptidic and nonpeptidic nature [ 11 ]. Whether the three groups found in pseudoscorpion venom are the culprit for neurotoxicity in rat brain is uncertain, because studies in spider venom have also shown the presence of polyamines targeting ionotropic glutamate receptors (e.g., [ 41 , 42 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its similarity to other agatoxins, a family of peptides including low mass molecular toxins with affinity to the sodium or calcium ion channels [ 40 ], suggest they might share similar functions. The only previous study on the effects of the crude venom of pseudoscorpion suggested the presence of putative neurotoxins of peptidic and nonpeptidic nature [ 11 ]. Whether the three groups found in pseudoscorpion venom are the culprit for neurotoxicity in rat brain is uncertain, because studies in spider venom have also shown the presence of polyamines targeting ionotropic glutamate receptors (e.g., [ 41 , 42 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, and in contrast to the remaining venomous arachnid groups, the composition of pseudoscorpion venom remains unknown. Santos et al [ 11 ] studied the effect of the crude venom from Paratemnoides elongatus on a rat cerebral cortex. Their findings were suggestive of the presence of selective compounds (e.g., neurotoxins) acting in l -glu and GABA dynamics, but no specific compounds were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudoscorpions (Arachnida: Pseudoscorpiones) are small (2-8 mm) predatory microarthropods that reach their peak species diversity in the tropics (Harvey 2007). Pseudoscorpions hunt other small arthropods, and those in the suborder Iocheirata paralyse their prey with venom from glands in their chelae (Dos Santos and Coutinho-Netto 2006). Wyochernes asiaticus (Arachnida: Pseudoscorpiones: Chernetidae) is the northernmost pseudoscorpion (Buddle 2015), living in Beringia, the region of what is now the Yukon Territory, Canada, Alaska, the United States of America, and parts of far eastern Russia that remained unglaciated in the last glacial maximum (Hopkins 1982).…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only a single experimental study into the effects of pseudoscorpion venom. This study showed that the crude venom of Paratemnoides elongatus affects the uptake and binding of neurotransmitter in rat brain preparations [ 139 ]. However, nothing at all is known about the composition of pseudoscorpion venom.…”
Section: Arthropodamentioning
confidence: 99%